2009
DOI: 10.1210/jc.2008-2606
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Gonadotropin-Releasing Hormone Pulse Generator Sensitivity to Progesterone Inhibition in Hyperandrogenic Adolescent Girls—Implications for Regulation of Pubertal Maturation

Abstract: Hyperandrogenism is variably associated with reduced GnRH pulse generator sensitivity to P-mediated slowing during adolescence. In addition to androgen levels, insulin resistance may modulate P sensitivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(52 citation statements)
references
References 23 publications
1
46
0
1
Order By: Relevance
“…Our sensitivity analysis, excluding girls with transient thelarche, showed similar (17). Furthermore, insulin resistance increases the levels of hyperandrogenemia (14), which in combination may facilitate the GnRH pulsatile secretion and increase pituitary secretion (37) and androgen secretion at the ovarian theca cells (16). Additionally, in adults, insulin and IGF1 stimulate breast cell division (7,8); thus, they could be involved in breast development in early puberty (9).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…Our sensitivity analysis, excluding girls with transient thelarche, showed similar (17). Furthermore, insulin resistance increases the levels of hyperandrogenemia (14), which in combination may facilitate the GnRH pulsatile secretion and increase pituitary secretion (37) and androgen secretion at the ovarian theca cells (16). Additionally, in adults, insulin and IGF1 stimulate breast cell division (7,8); thus, they could be involved in breast development in early puberty (9).…”
Section: Resultsmentioning
confidence: 74%
“…First, obesity may trigger central gonadotropin secretion by increasing leptin levels that play a permissive role in gonadotropin secretion (13). Another possibility is that insulin resistance increases adrenal androgen concentration in blood (14,15), which in combination with insulin and leptin may further facilitate GnRH pulsatile secretion and thus increase androgen synthesis by ovarian theca cells (16). Alternatively, circulating sex steroid hormones can be higher in obese children due to increased aromatase activity, leading to peripheral conversion of androgens to estrone and estradiol (11).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that increased androgen concentrations in prepubertal girls could facilitate a pubertal increase in GnRH secretion, possibly leading to early pubertal onset [78]. Leptin and insulin functions in various target tissues are shown in Figure 1.…”
Section: Sex Hormones and Growth During Pubertymentioning
confidence: 99%
“…puberty) and pathological conditions [93,94,95]. In a recent study, the expression of P 4 receptor membrane component 1 (PgRMC1) and its partner SERPINE1 mRNA-binding protein 1 (SERBP1) has been shown in GnRH neurons.…”
Section: Discussionmentioning
confidence: 99%